2015
DOI: 10.1071/wf12213
|View full text |Cite
|
Sign up to set email alerts
|

Predicting delay in residents’ decisions on defending v. evacuating through antecedents of decision avoidance

Abstract: In the event of a wildfire, Australian residents of wildfire-prone areas have a choice to defend their home or evacuate early. However, rather than deciding on and preparing for one of these fire-responses ahead of time, most residents delay deciding on defending v. evacuating (e.g. they wait and see instead). Recent research has shown that delaying this decision is associated with reduced levels of preparedness for both responses and on the day of a fire, an increased risk to life and property. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…However, the majority of Australian articles focus on homeowner decision-making during a fire [13,57,[64][65][66][67][68][69].…”
Section: Experiencing and Recovering From A Wildfirementioning
confidence: 98%
See 1 more Smart Citation
“…However, the majority of Australian articles focus on homeowner decision-making during a fire [13,57,[64][65][66][67][68][69].…”
Section: Experiencing and Recovering From A Wildfirementioning
confidence: 98%
“…Interestingly, initial research to understand this delayed decision-making has shown that risk perception is not influential in this choice. Rather people who plan to wait and see tend to see equal benefits between evacuating and defending their property [68].…”
Section: Experiencing and Recovering From A Wildfirementioning
confidence: 99%
“…Practical response over many years to awareness campaigns is widely acknowledged to be poor [9, 10, 12, 34, 77, 87, 88]. Figures reported by the South Australian Country Fire Service in their Annual Reports do indicate improvement, but numbers clearly demonstrate the persistently low correlation between awareness and positive behaviour change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study found that uncertainty about where the fire was located and how severe the risks might be led many to take a wait and see approach during the Black Saturday fires, only evacuating when some external event signaled that decisive action was needed, which was often an official or physical cue . Subsequent survey work found that respondents who saw staying and leaving as equally attractive options were less likely to indicate a clear plan to either stay and defend or leave early …”
Section: Literature Reviewmentioning
confidence: 99%